Lexical borrowings in the Polish dialect used in the South-Eastern Borderlands (on the basis of Trembowla and Wierzbowiec) - Kostecka-Sadowa, Anna (Papers in Linguistics, 2019)
In the article the author presents some lexical material from the dictionary of the Polish dialect used in the South-Eastern Borderlands (on the basis of Trembowla and Wierzbowiec) and discusses some borrowings, which became part of the dialect as a result of direct contact between three languages: Polish, Ukrainian and Russian.